Remote regulation of type 2 immunity by intestinal parasites. (March 2021) - Popple, S.J.; Burrows, K.; Mortha, A.; Osborne, L.C.
Abstract: The intestinal tract is the target organ of most parasitic infections, including those by helminths and protozoa. These parasites elicit prototypical type 2 immune activation in the host's immune system with striking impact on the local tissue microenvironment. Despite local containment of these parasites within the intestinal tract, parasitic infections also mediate immune adaptation in peripheral organs. In this review, we summarize the current knowledge on how such gut-tissue axes influence important immune-mediated resistance and disease tolerance in the context of coinfections, and elaborate on the implications of parasite-regulated gut-lung and gut-brain axes on the development and severity of airway inflammation and central nervous system diseases.